Senyapan Pada Ujaran Iwan Fals di Acara Talkshow Kick Andy “Akhirnya Iwan Fals Bicara” - Dian Lufia Rahmawati (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2014)
Paused phenomenon needs to be studied through research that is useful to add information about the disciplines of speech production psycholinguistics. The focus of this research are: (1) what percentage of paused that occur during Iwan Fals deliver answers?; (2) What kind paused happened?; and (3) what is the reason or cause of pause? This study used a qualitative approach and descriptive analysis method. The research objectives are recording the show Kick Andy